1985
DOI: 10.1063/1.335566
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and x-ray diffraction in narrow-band-gap InAs/GaSb superlattices

Abstract: We report on the optical transmission properties of narrow-band-gap (Eg<0.1 eV) InAs/GaSb superlattices grown by molecular-beam epitaxy. Energy band gaps of 0.15 and 0.085 eV at 4.8 K are determined for a 102-Å-period and a 124-Å-period superlattice, respectively. The absorption edge is extremely soft due to the spatial mismatch of hole and electron wave functions. In addition we show the first reported x-ray diffraction measurements on this materials system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The conduction-band (CB) minimum of InAs is lower in energy than the valence-band (VB) maximum of GaSb. It was observed that, in the study of (InAs) 1 . x (GaAs) x -(GaSb) 1 .…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The conduction-band (CB) minimum of InAs is lower in energy than the valence-band (VB) maximum of GaSb. It was observed that, in the study of (InAs) 1 . x (GaAs) x -(GaSb) 1 .…”
Section: Introductionmentioning
confidence: 92%
“…It was observed that, in the study of (InAs) 1 . x (GaAs) x -(GaSb) 1 . y (GaAs) y p-n heterojunctions [22], the rectifying characteristic changes to nonrectification as both x and y approach zero, implying the change-over from the "staggered" heterojunction to the -"misaligned" one.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The InAs-GaSb SL is composed of thin alternating InAs and GaSb layers that utilize quantum confinement to vary its bandgap by varying the SL periodicity, while the strained InAs-GaInSb SL employs quantum confinement and strain effects to vary its bandgap and optical characteristics. Intensive research over the past two decades has led to significant progress (3)(4)(5)(6)(7)(8) in understanding the characteristics of type II SL photodiodes. However, type II SL photodetectors have not realized their predicted performance (2, 9) expectations, which are based on the intrinsic characteristics of type II GaSb/InAs SLs.…”
Section: Introductionmentioning
confidence: 99%